The investigation of adaptogenic, hypoglycemic and hepatoprotective properties of Clitoria ternatea L. on experimental models in vivo - Hubich, Aksana I.; Bandyk, Yanina A.; Zalesskaya, Natalya A.; Okarakava, Svyatlana S.; Kapanic, Alena I.; Herasimava, Alina E. (Experimental Biology and Biotechnology, 2020)
This work is devoted to the study of the effect of Clitoria ternatea L. decoction for energy and carbohydrate metabolism in conditions of increased physical activity, the analysis of possibilities carbohydrate and lipid metabolism markers correcting in a model of experimental hyperphagia and experimental diabetes, and the efficiency of the stabilization of liver injury and lipid peroxidation markers in rats in an experimental model of chronic alcohol intoxication. It’s established that Clitoria ternatea L. has a stabilizing effect on carbohydrate metabolism in rats with experimental diabetes and hyperphagia, exhibits antioxidant and hepatoprotective effect in rats with experimental alcoholic liver, comparable to the action of classical hepatoprotector «Hepsil-Rn», has adaptogenic effect in experimental model of physical activity, comparable to the energy drink «Burn». The effect of the prepatation tested was more pronounced under alloxan diabetes than the effect of the anti-diabetic «Sadifit» collection. The results obtained may be due to the presence of flavonoids, ascorbic acid, tannins and unsaturated fatty acids, exhibiting an antioxidant effect, as well as glycosides, terpenes and diterpenes, contributing to increased permeability of cell membranes for glucose.